Impact of agricultural science and technology innovation resources allocation on rural revitalization - Wu, Guosong; Wang, Yuanyuan; Yao, Sheng (Frontiers in Sustainable Food Systems, 2024)
China's reform began in the countryside, and rural reform began in Anhui.This study uses Anhui Province, China as an example in analysing the impact of agricultural science and technology innovation resource allocation on rural revitalisation, particularly by constructing an econometric model. Results indicate that the allocation of agricultural science and technology innovation resources has a steady positive impact on rural revitalisation. Improvements in the allocation of agricultural science and technology innovation resources can effectively promote the development of rural revitalisation and the spatial spillover of rural development, thereby facilitating the promotion of the spillover of neighbouring areas to local rural development. A nonlinear relationship exists between allocation of agricultural science and technology innovation resources and rural revitalisation. Lastly, rural revitalization can only be promoted substantially when the allocation of agricultural science and technology innovation resources reaches a certain condition.